Law of the Sea. - Glassner, Martin Ira (1989)
Keywords: dept.egm; faculty_collection; sabbatical_report

Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Academic Publishers, 1986)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; Bibliography; Marine resources conservation; Law and legislation; dept.egm; faculty_collection

International Law of the Sea and Marine Affairs: A Bibliography. Supplement to the 1980 Edition - Papadakis, N.; Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Boston, 1984)
Keywords: Bibliography; Maritime law; dept.egm; faculty_collection

Global Resources: Challenges of Interdependence - Glassner, Martin Ira (Published for the Foreign Policy Association by Praeger, 1983)
SCSU Faculty Scholar Award
Keywords: Natural resources; award_winner; dept.egm; faculty_collection

Baseline Shellfish Data for the Assessment of Potential Environmental Impacts Associated with Energy Activities in Connecticut's Coastal Zone - Pellegrino, Peter Edward; Hubbard, William A. (Southern Connecticut State University Foundation, 1983)
Keywords: Connecticut Coastal Energy Impact Program; Shellfish populations; Effect of oil spills on; Environmental aspects; Long Island Sound (N.Y. and Conn.); Long Island Sound (N.Y. and Conn.); Aquatic ecology; Long Island Sound (N.Y. and Conn.); Energy industries; Long Island Sound (N.Y. and Conn.); Petroleum products; Long Island Sound (N.Y. and Conn.); Shellfish; Research; dept.egm; faculty_collection

Bibliography on Land-Locked States - Glassner, Martin Ira (Sijthoff & Noordhoff, 1980)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Maritime law; dept.egm; faculty_collection

Systematic Political Geography - Glassner, Martin Ira; De Blij, Harm J. (Wiley, 1980)
Keywords: Political geography; Geopolitics; dept.egm; faculty_collection

The Life and Thought of Isaiah Bowman. - Martin, Geoffrey J. (1980)
SCSU Faculty Scholar Award
Keywords: Biography; Bowman; Isaiah; 1878-1950; Geographers; United States; award_winner; dept.egm; faculty_collection

Systematic political geography. 4th edition - Glassner, M.I.; De Blij, H.J. (Systematic political geography. 4th edition, 1988)
The fourth edition of this text has been thoroughly updated and includes expanded chapters on Antarctica and outer space as well as new chapters on the geography of elections and the geography of war and peace. A chapter is devoted to outlaws and merchants of death which covers piracy, drug trafficing, the arms trade, and terrorism. Other additions include coverage of international economic sanctions, transnational corporations, refugees, and pollution across international boundaries. -from Publisher
Keywords: arms trade; dept.egm; economic sanctions; elections; peace; political geography; pollution; refugees; terrorism; war; ⛔ No DOI found

Classifying Aquatic Habitats - Smith, D.G.; Leskowitz, I. (American Biology Teacher, 1987)
1 citations (Crossref) [2023-10-31]
Keywords: dept.egm

John Paul Goode, 1862-1932. - Martin, G.J. (Geographers: biobibliographical studies, vol. 8, 1984)
In 1901 Goode obtained his doctorate - only the second in the USA to break away from the geology/physiography tradition. As his career developed he increasingly specialized in cartography, developed coloured wall maps for Rand McNally, and an interrupted homolosine projection. His name has survived on a school atlas for over 60 years. There is a chronological bibliography and a summary of his life.-K.Clayton
Keywords: dept.egm; ⛔ No DOI found

Geography in Peru - Yacher, Leon (The Professional Geographer, 1989)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-013-298-750-435 tex.type: [object Object]
Keywords: dept.egm

On whittlesey, bowman and harvard - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/194-741-197-626-019 tex.type: [object Object]
Keywords: dept.egm

Preston E. James, 1899–1986 - Martin, Geoffrey J (Annals of The Association of American Geographers, 1988)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/034-021-593-801-31X tex.type: [object Object]
Keywords: dept.egm

Against presentist histories: solot's view of sauer - Speth, William W (Annals of The Association of American Geographers, 1987)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-534-127-566-295 tex.type: [object Object]
Keywords: dept.egm

The ecologic tradition in american geography 1895–1925 - Martin, Geoffrey J (Canadian Geographer, 1987)
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-877-891-516-111 tex.type: [object Object]
Keywords: dept.egm

On the discrimination of Anthropo‐Geocraphies - Speth, William W (Canadian Geographer, 1987)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/074-321-118-839-576 tex.type: [object Object]
Keywords: dept.egm

Paradigm change: a history of geography in the United States, 1892-1925. - Martin, G.J. (National Geographic Research, 1985)
The third of 5 paradigm periods posited for the history of American geography extends from the establishment of the Committee of Ten in 1892, to the publication of Carl Sauer's 'The Morphology of Landscape' in 1925. This period witnessed the emergence of discipline and profession - an inert physiography, energized by the discipline-forming Davisian cycle of erosion, preceded the causal notion. Determinisms that gave way to studies of control, adjustment, and the geographic factor, provided a framework for the geographic philosophies of such scholars as Albert Perry Brigham, Ellsworth Huntington, and Ellen Semple. Regional delimitations of physiographic provinces and variant forms of economic geography emerged as alternatives to causality. The geography of France, Germany, and Britain afforded little support for varieties of determinism in America, and was further questioned during the 1914-1918 war years. Meanwhile, Wellington D. Jones and Carl O. Sauer developed another viewpoint, adumbrated by Sauer in a series of papers culminating in 'The Morphology of Landscape'. The locus of American geography had been moved.-Author
Keywords: dept.egm; ⛔ No DOI found

Preservation of the history of geography - Martin, G.J. (Journal of Geography, 1985)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

New haven, connecticut, from the air - Richason, F Benjamin; Yacher, Leon (Journal of Geography, 1981)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-405-597-813-713 tex.type: [object Object]
Keywords: dept.egm

Book Reivew: Maritime boundaries and ocean resources: Gerald Blake (ed.), Croom Helm, Beckenham, Kent, 1987, xiii + 284 pp., £27.50 - Glassner, Martin I. (Political Geography Quarterly, 1989)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book review: International and United States documents on oceans law and policy: John Norton Moore (ed.), William S. Hein, Buffalo, NY, 1986, 5 vols., $195.00 - Glassner, Martin I. (Political Geography Quarterly, 1989)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book Review: The refugee problem on universal, regional and national level: Thesaurus Acroasium, Vol. XIII, Institute of International Public Law and International Relations of Thessaloniki, 1987, xvi + 1022pp., $150.00 - Glassner, Martin I. (Political Geography Quarterly, 1989)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book review: Geopolitics of the Caribbean: Ministates in a wider world: T.D. Anderson, Praeger, New York, 1984, xiii + 175 pp., $26.95 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book review: National interests and the military use of space: W.J. Durch (ed.), Ballinger, Cambridge, Mass, 1984, xiv + 304 pp., $28.00 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

The new political geography of the sea - Glassner, Martin Ira (Political Geography Quarterly, 1986)
The political geography of the sea may be defined as that portion of the Law of the Sea which has a spatial or territorial component, including such matters as the territorial sea and the contiguous zone, the exclusive economic zone, international straits, the regimes of islands and archipelagos, freedom of transit for land-locked states, deep seabed mining and protection and preservation of the marine environment. It also includes larger issues not formally part of the Law of the Sea, such as the links between the Law of the Sea and Antarctica, and military uses of the sea. The new Law of the Sea (hence the new political geography of the sea) is the latest stage in a long evolution traceable to the ancient Greeks and Romans but accelerating since the 17th century. The United Nations Conference on the Law of the Sea produced in 1958 four conventions essentially codifying the existing Law of the Sea, including the new continental shelf doctrine. They were followed by the 1965 UN Convention on Transit Trade of Land-locked States. All soon proved inadequate, unacceptable or obsolescent. The Third United Nations Conference on the Law of the Sea (UNCLOS III, 1973-1982) produced a new single, comprehensive convention embodying nearly all old and new aspects of the Law of the Sea. This and related matters deserve much greater attention from political geographers than they have received thus far. © 1986.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-537-247-901-750 tex.type: [object Object]
Keywords: dept.egm

Political geography of contemporary events VII: The view from the near north— South Americans view Antarctica and the Southern Ocean geopolitically - Glassner, Martin Ira (Political Geography Quarterly, 1985)
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/041-429-628-526-147 tex.type: [object Object]
Keywords: dept.egm